2003
DOI: 10.1093/aob/mcg201
|View full text |Cite
|
Sign up to set email alerts
|

Floral Structure, Breeding System and Fruit-set in the Threatened Sub-shrub Tetratheca juncea Smith (Tremandraceae)

Abstract: Tetratheca juncea Smith (Tremandraceae) has undergone a range contraction of approx. 50 km in the last 100 years and is now listed as a vulnerable sub-shrub restricted to the central and north coast regions of New South Wales, Australia. There are approx. 250 populations in a 110 km north-south distribution and populations are usually small with fewer than 50 plants/clumps. The reproductive ecology of the species was studied to determine why seed-set is reportedly rare. Flowers are bisexual, odourless and nect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Our results are in contrast to those of many studies that have shown negative eVects of remnant size on reproduction in small populations of native plants (Jennersten 1988;Aizen and Feinsinger 1994;Ågren 1996;Morgan 1999;Brys et al 2004), but are in agreement with others that have found no eVects or only intermittent eVects of size (Heschel and Paige 1995;Alexandersson and Ågren 1996;Molano-Flores and Hendrix 1999;Gross et al 2003).…”
Section: Discussionsupporting
confidence: 83%
“…Our results are in contrast to those of many studies that have shown negative eVects of remnant size on reproduction in small populations of native plants (Jennersten 1988;Aizen and Feinsinger 1994;Ågren 1996;Morgan 1999;Brys et al 2004), but are in agreement with others that have found no eVects or only intermittent eVects of size (Heschel and Paige 1995;Alexandersson and Ågren 1996;Molano-Flores and Hendrix 1999;Gross et al 2003).…”
Section: Discussionsupporting
confidence: 83%
“…paynterae these extrinsic factors, together with partial self-incompatibility are likely to be more important in limiting selfing than physical features of the flower as suggested by Gross et al (2003) for the rare east coast endemic T. juncea. Pollination studies revealed T. juncea was self-compatible but preferentially outcrossing.…”
Section: Discussionmentioning
confidence: 93%
“…The numbers of flowers per treatment are listed in Table 1. The stigma in Tetratheca species is small (0.02 mm wide in T. juncea; Gross et al 2003) and pollen was therefore deposited, using a dissecting needle, on both the tip and sides of the style that were protruding from the anther whorl. A micro-dissecting head lens was used to check that pollen had been transferred.…”
Section: Location and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive ecology is of fundamental importance in determining the barriers to production of reproductive propagules and is of pivotal significance in formulating strategies for the conservation of taxa (Gross et al 2003;Tandon et al 2003), particularly with small population sizes . Because of unprecedented increases in anthropogenic causes of population decline, conservation biologists have extensively studied the effects of small population size on demography (Menges 1991), reproductive success (Young & Brown 1998) and genetic variation (Prober & Brown 1994).…”
Section: Introductionmentioning
confidence: 99%